Análise do estudo da modelagem e do controle do pêndulo invertido para fins educacionais - Kato, Emilia Harumi (2023)
Engineering courses have a significant number of theoretical classes, with only a small portion dedicated to practical applications of the concepts studied. In light of this, the use of educational tools, such as simulators, becomes indispensable as a teaching methodology to provide practical situations to the students. This can be applied to subjects that involve the study of control of dynamic and nonlinear systems, among others, which are part of the electronic engineering curriculum. Thus, this this thesis will analyse three control methods, Linear Quadratic Regulator (LQR), logic Fuzzy and Proportional Integral Derivative (PID), in order to stabilize a system of inverted pendulum over a moving cart and compare the results of each one on Matlab and python language, so that the results and codes can be used to show how the theories learned during classes can be used on the same problem.